Is hatchery stocking a help or harm? : Evidence, limitations and future directions in ecological and genetic surveys - Araki, Hitoshi; Schmid, Corinne (Aquaculture, 2010)
Hatchery fish stocking for stock enhancement has been operated at a massive and global scale. However, the use of hatchery fish as a means of stock enhancement is highly controversial, and little is known about its effects on wild stock and consequences for stock enhancement. Here we review the scientific literature on this subject in order to address a fundamental question — is hatchery stocking a help or harm for wild stock and stock enhancement? We summarized 266 peer-reviewed papers that were published in the last 50years, which describe empirical case studies on ecology and genetics of hatchery stocks and their effects on stock enhancement. Specifically, we asked whether hatchery stock and wild stock differed in fitness and the level of genetic variation, and whether stocking affected population abundance. Seventy studies contained comparisons between hatchery and wild stocks, out of which 23 studies showed significantly negative effects of hatchery rearing on the fitness of stocked fish, and 28 studies showed reduced genetic variation in hatchery populations. None of these studies suggested a positive genetic effect on the fitness of hatchery-reared individuals after release. These results suggest that negative effects of hatchery rearing are not just a concern but undeniably present in many aquaculture species. In a few cases, however, no obvious effect of hatchery rearing was observed, and a positive contribution of hatchery stock to the abundance of fish populations was indicated. These examples suggest that there is a chance to improve hatchery practices and mitigate the negative effects on wild stocks, although scientific data supporting the positive effect on stock enhancement are largely missing at this moment. Technically, microsatellite-based parentage assignments have been proven as a useful tool for the evaluation of reproductive fitness in natural settings, which is a key for stock enhancement by hatchery-based stocking. We discuss implications of these results, as well as their limitations and future directions.